2012
DOI: 10.1152/ajpregu.00214.2011
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y gastric bypass in rats increases sucrose taste-related motivated behavior independent of pharmacological GLP-1-receptor modulation

Abstract: Roux-en-Y gastric bypass (RYGB) surgery has been shown to decrease consummatory responsiveness of rats to high sucrose concentrations, and genetic deletion of glucagon-like peptide-1 receptors (GLP-1R) has been shown to decrease consummatory responsiveness of mice to low-sucrose concentrations. Here we assessed the effects of RYGB and pharmacological GLP-1R modulation on sucrose licking by chow-fed rats in a brief-access test that assessed consummatory and appetitive behaviors. Rats were tested while fasted pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 72 publications
4
50
2
Order By: Relevance
“…Hence, RYGB rats liked the low concentrations of sucrose and fat more than sham-operated rats, at least under some conditions. In our own studies, however, we found no decrease in the concentration-dependent licking response to sucrose in chowfed RYGB rats; to our surprise, RYGB rats actually approached the drinking spouts more often than sham rats, indicating an increased appetitive behavior (83). The reasons for the partly discrepant results across studies is not entirely clear, but may depend on the exact test paradigm, prior experience of the animals with the taste stimulus, the obesity state of the animals, their feeding paradigm and diet, and perhaps differences in the surgical technique, such as size of the gastric pouch.…”
Section: Taste and Food Preferencescontrasting
confidence: 65%
See 3 more Smart Citations
“…Hence, RYGB rats liked the low concentrations of sucrose and fat more than sham-operated rats, at least under some conditions. In our own studies, however, we found no decrease in the concentration-dependent licking response to sucrose in chowfed RYGB rats; to our surprise, RYGB rats actually approached the drinking spouts more often than sham rats, indicating an increased appetitive behavior (83). The reasons for the partly discrepant results across studies is not entirely clear, but may depend on the exact test paradigm, prior experience of the animals with the taste stimulus, the obesity state of the animals, their feeding paradigm and diet, and perhaps differences in the surgical technique, such as size of the gastric pouch.…”
Section: Taste and Food Preferencescontrasting
confidence: 65%
“…Further, RYGB rats seem to initiate more licking behavior to sweet or fat stimuli in brief access tests (83). Together, these results indicate that reduced eating after RYGB seems to be a voluntary process that is not guided by an inability or unwillingness to approach food or to ingest but that may be related to (enhanced) mechanisms of satiation, i.e., once food ingestion has started.…”
Section: Clinical Effect 2: Change Of Eating Behaviormentioning
confidence: 73%
See 2 more Smart Citations
“…Indeed, the detectability of sugar is heightened after RYGB in humans, but this does not seem to translate to a reduced hedonic value of sweet foods and fluids (3,4). Also, the results of brief-access tests or examinations of early-meal lick patterns, in which the postingestive consequences of nutritive stimuli are limited, are not always indicative of blunted avidity for sucrose or Intralipid by RYGB rats (14,17,18; though see 8,27,32). More to the point, the motivation to complete an operant work demand in a progressive ratio task is not decreased by RYGB in rats when sucrose or Intralipid are used as reinforcers, even after these rats displayed blunted and/or progressively decreasing preference for these stimuli in long-term tests (16).…”
mentioning
confidence: 99%